Prenatální diagnostika tuberózní sklerózy zalozená na znalosti kauzální mutace - Vrtel, R; Vodicka, R; Santavá, A; Santavý, J; Krejciríková, E (Casopis lekaru ceskych, 2006)
BACKGROUND: Tuberous sclerosis is an autosomal-dominant disease characterised by development of benign growth - hamartomas in different organs. Disorder is caused by mutations affecting either of the tumor-suppressor genes, TSC1 or TSC2. Quest for causing mutations is very difficult due to their random distribution over the genes. METHODS AND RESULTS: Article refers on accomplishment of the first tuberous sclerosis prenatal diagnostics in Czech Republic based on knowledge of causing mutation. Foetal DNA sample, obtained in 13th week from Q435X family pregnant woman, was analyzed by DGGE method. CONCLUSIONS: Examination excluded presence of tested TSC1 gene defect in an offspring.
Keywords: Tumor Suppressor Proteins; Tuberous Sclerosis Complex 2 Protein; Prenatal Diagnosis; Humans; nádorové supresorové proteiny; Female; Pedigree; Genes, Tumor Suppressor; lidé; Tuberous Sclerosis; rodokmen; ženské pohlaví; tumor supresorové geny; těhotenství; tuberin; tuberózní skleróza; mutace; Mutation; Pregnancy; prenatální diagnóza; Tuberous Sclerosis Complex 1 Protein; hamartin